Treat-to-target SLE strategy in 10 years: Discussion of current limitations and available options for implementation in real-world clinical practice - E. A. Aseeva; S. K. Solovyev; E. A. Pletnev; G. M. Koilubaeva; B. G. Issayeva; E. L. Nasonov (Научно-практическая ревматология)
In January 2013, at the initiative of the world’s leading rheumatologists Ronald F. van Vollenhoven, Josef Smolen, Marta Mosca and Matthias Schneider, a project was launched to create the “Treat-to-Target” concept for systemic lupus erythematosus (SLE). In 2014, the group published recommendations “Treat-to-Target for SLE”. The article discusses the problems of implementing the strategy in real clinical practice and discusses the proposed ways of its implementation, proposed by international experts in 2025: 5 basic principles and 11 statements.